Penerapan Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar IPA Siswa Kelas IVB SDN 004 Teratak Buluh - Muharmi, Muharmi; Daud, Damanhuri; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractBackground problem in this study is the low science learning outcomes of students with an average value of 63.75 with a minimum completeness criteria ( KKM ) for learning science is 65 , where around 20 students only 9 students who achieve KKM and 11 students who did not achieve KKM . To overcome these problems , one of the models of learning that can improve student learning outcomes IPA is terbiming inquiry learning model which guided inquiry learning model is a learning model that emphasizes the process of thinking critically and analytically students to seek and find their own answer to a problem raised , so that the process pembelajara student-centered and teacher as facilitator . The purpose of this research is to improve the learning outcomes of students grade IVB IPA SDN 004 reed hut are 20 people with the structure of matter and uses parts of the plant . With the formulation of the problem : Is the Application Model to Improve Outcomes pembelajran InkuiriTerbimbing Science Class IVB Grade Students of SDN 004 reed hut . This thesis presents the results of student learning obtained from daily tests I Cycle I , II daily test cycle II , III and daily test cycle III . In the first cycle , the average value of student learning outcomes is 65.25 . Cycle II , the average value of 68.75 student learning outcomes , and the third cycle with an average value of 74.25 . Thus , the increase in the average value of the first cycle to the second cycle was 5.36 % and an increase in the average value of the second cycle to cycle III is 8.00 % . The results of the analysis of learning activities for students and teachers in classroom learning takes place IVB SDN reed hut is 004 students with learning activities guided inquiry in the first cycle with an average of 68.95 % either category , the second cycle average of 80.36 % categorized as very good and the third cycle average 94.65 % excellent categories and activities of teachers in fostering the learning process in the first cycle an average of 75.83 % second cycle either category average of 83.75 % is very good category and third cycle average average 95 % very good category . SDN 004 tdi research results prove that the reed hut application of guided inquiry learning model to improve learning outcomes of students grade IVB 004 IPA IPA reed hut .Keywords : Guided Inquiry , Learning Outcomes